Resource-Saving Methods for Growing Rice in the Krasnodar Territory - Prikhodko Igor (EDP Sciences, 2021)
The world practice of rice cultivation has shown that rice cultivation by traditional methods for Russia is labor-intensive, resource-intensive, ineffective with low profitability, and often unprofitable production. As a result, traditional methods of flooding rice paddies in Russia are faced with a shortage and high cost of irrigation water and a reduction in rice irrigation systems, i.e., areas suitable for rice cultivation. For solving the problem of unprofitable rice production, an analysis of the world practice of rice production has been implemented. The analysis showed that the most optimal solution for the natural and climatic conditions of the Krasnodar Territory is the cultivation of rice using sprinkler irrigation and drip irrigation. Further analysis showed that drip irrigation is the most promising way of growing rice, which has many undeniable advantages. The main advantages of drip irrigation are the low irrigation rate, labor intensity, and energy intensity of rice production. Therefore, the article proposes a pioneering Russian ridge cultivation method for rice cultivation on the lands of the irrigated rice fund with drip irrigation under plastic and/or biodegradable perforated film. This method will make it possible to radically revise the principles of rice cultivation, form a new generation of rice crop rotations with the inclusion of melons and vegetables in them, and carry out rice production on previously rainfed lands. The implementation of the method has proven the effectiveness and feasibility of our research.